Efficacy and safety of alogliptin for glucocorticoid-induced hyperglycemia in patients with autoimmune-diseases: A retrospective analysis - Ito, Satoshi; Asano, Ryoko; Hasegawa, Eriko; Tobe, Kazuyuki; Ishikawa, Hajime; Taki, Hirofumi; Murasawa, Akira; Kobayashi, Daisuke; Narita, Ichiei; Higasitani, Kana; Nakazono, Kiyoshi (Clinical Rheumatology and Related Research, 2020)
Objective:  The purpose of this study was to examine the efficacy and safety of alogliptin in subjects with glucocorticoid-induced hyperglycemia and autoimmune diseases.   Methods:  The subjects were 101 patients who started alogliptin for glucocorticoid-induced hyperglycemia at Niigata Rheumatic Center from January 2011 to October 2017. The clinical parameters and adverse events after the initiation of alogliptin were analyzed retrospectively. We conducted subgroup analyses to determine the effect of alogliptin alone for the treatment of hyperglycemia as well as its effect on rheumatoid arthritis（RA）. Wilcoxon signed-rank test was used to analyze clinical outcomes.   Results:  Seventy-four patients were enrolled（Group 1）. After treatment with alogliptin, hemoglobin A1c（HbA1c）was significantly reduced at 24 weeks（7.10 to 6.50, p=0.00000818）. In Group 2（n=57）, which consisted of patients who used a fixed dose of a glucocorticoid and antidiabetic agents, HbA1c was significantly reduced at 24 weeks（7.10 to 6.50, p=0.000467）. In Group 3（n=22）, which consisted of patients who used a fixed dose of a glucocorticoid and anti-rheumatic drugs, there were no significant differences in any clinical parameter for arthritis. No patients dropped out due to exacerbation of arthralgia. Two of 22（9%）patients had worsened RA activity, but continued alogliptin.   Conclusion:  These results suggest that alogliptin was effective in the treatment of glucocorticoid-induced hyperglycemia, and was associated with few adverse effects. Although there were no significant differences in any clinical parameter for arthritis during the study, we should monitor RA activity after administration of dipeptidyl peptidase-4 inhibitors in patients with RA.